Modeling of reference schemes - Halpin, Terry (Springer Berlin Heidelberg, 2013)
In natural language, one usually refers to objects by means of proper names or definite descriptions. Languages for data modeling and/or ontology modeling vary considerably in their support for such natural reference schemes. An understanding of these differences is important both for modeling reference schemes within such languages and for transforming models from one language to another. This paper provides a critical and comparative review of reference scheme modeling within the Unified Modeling Language (version 2.5), the Barker dialect of Entity Relationship modeling, Object-Role Modeling (version 2), relational database modeling, and the Web Ontology Language (version 2.0). We identify which kinds of reference schemes can be captured within specific languages as well as those reference schemes that cannot be. Our analysis covers simple reference schemes, compound reference schemes, disjunctive reference and context-dependent reference schemes.